Experimental Analysis of Accuracy and Precision in Displacement Measurement Using Millimeter-Wave FMCW Radar - Hajime Takamatsu; Nariteru Hinohara; Ken Suzuki; Fuminori Sakai (Applied Sciences)
Millimeter-wave radar is emerging as a key sensor technology not only for autonomous driving but also for various industrial applications, such as vital sign monitoring and structural displacement sensing using millimeter-wave FMCW radar, which must detect extremely small displacements on the sub-micron scale. Accurate displacement measurements fundamentally rely on obtaining precise intermediate frequency (IF) phase data over slow time (i.e., chirp-to-chirp intervals or pulse repetition time) generated by the radar sensor system. In this study, we developed a millimeter-wave FMCW radar sensor for displacement sensing using a 77–81 GHz radar transceiver MMIC (Monolithic Microwave Integrated Circuit) and evaluated its accuracy and precision through a series of experiments. First, we assessed the MMIC’s phase performance under static conditions using a rigid RF waveguide, and second, we measured a vibrating target using an industrial vibration shaker as a reference. The experiments demonstrated a maximum accuracy error of +0.359 degrees (1.907 μm displacement) and a maximum 3-sigma precision of ±0.358 degrees (±1.180 μm displacement), validating the feasibility of using millimeter-wave radar to measure very small displacements.